RANCANGAN STRATEGI BISNIS PT GAMMA MITRA LESTARI SEBAGAI DISTRIBUSI RADIOFARMAKA DAN ALAT KESEHATAN FASILITAS KEDOKTERAN NUKLIR (UNIB Press, 2025)
This study aims to design a strategy for the company to face competition in the pharmaceutical distribution business in nuclear medicine facilities. As a company that acts as an importer, PT Gamma Mitra Lestari faces the challenge of intense competition with several competitors who have direct distribution power. This research uses a qualitative approach with an in-depth interview method with the company's key person to identify internal and external factors that affect business strategy. External factor analysis was conducted using the PESTEL model and Porter's Five Forces, while internal analysis used the VRIO framework to assess the company's resources and capabilities. The results revealed that PT Gamma Mitra Lestari has advantages in terms of relationships with suppliers and product quality, but is still limited in terms of efficient distribution channels. Based on these findings, the suggested strategies include improving market education to expand technology adoption and raise awareness related to nuclear medicine in new hospitals, supplier diversification to reduce the risk of dependence on a single supplier, and collaboration with BRIN and leading hospitals to develop products and meet local market needs with high TKDN. This research provides implications for other nuclear medicine industry players in designing adaptive and sustainable business strategies.